EXAMINING THE IMPACT OF E-WOM, CUSTOMER EXPERIENCE, AND CUSTOMER TRUST ON CUSTOMER ENGAGEMENT: AN ONLINE RETAIL BUSINESS PERSPECTIVE - Setiyawami, Setiyawami; Setyawati, Christina Yanita; Pandey, Deeak; Kaur, Simran (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
Online business, which is increasingly rapid in the current digital era, requires companies to innovate in customer service. Strong e-WOM can shape customers' positive perceptions of a brand, while good customer experience will increase satisfaction and loyalty. Customer trust is important in building long-term relationships with brands and influencing customer engagement in digital marketing activities. This research aims to analyze the influence of e-WOM, customer experience, and customer trust on customer involvement in online retail businesses. This research uses a quantitative approach with a survey method to collect data from 180 respondents who are active customers on online retail platforms in Indonesia. The sample was selected using a purposive sampling technique with the criteria of customers who had purchased and provided reviews about products or services using an online questionnaire as a data collection instrument. The research results show that e-WOM, customer experience, and customer trust positively and significantly affect customer engagement. Positive e-WOM increases customers' interest in interacting with the brand while satisfying customer experiences and strengthening loyalty. These findings provide implications for online retail businesses to further optimize digital marketing strategies by strengthening e-WOM, improving the quality of customer experience, and building trust to increase customer engagement.